Drawing Dangerous Women: The Monstrous-Feminine, Taboo and Japanese Feminist Perspectives on the Female Form - Sara Sylvester (Feminist Encounters: A Journal of Critical Studies in Culture and Politics, 2020)
During the twenty-first century, global developments with graphic texts have seen positive changes in the representation of characters and storylines representing female-led narratives and perspectives. Recent Japanese graphic texts offer an instructive window into concerns about feminist comics and graphic novels which not only represent a vital intervention in terms of contemporary Japanese feminist politics but also reinforce their relevance as feminist art activism within a global frame. Taking into account the popularity of manga worldwide this article argues that the growing range of Japanese texts with clear feminist messages marks an intervention on behalf of female creators in keeping with the theory and practice of contemporary feminist discourse. Additionally, this Japanese evolution illustrates the ways in which second wave feminism, particularly feminist art, has impacted women on a global scale. Consequently, the article explores the important role of intersectionality alongside themes relating to the body and sexuality, subversion of the monstrous feminine, feminist activism by considering the narrative of Rokudenashiko’s graphic memoir What is Obscenity?: The story of a good for nothing artist and her pussy (2016).